2023
DOI: 10.3389/fpsyg.2023.1052877
|View full text |Cite
|
Sign up to set email alerts
|

Measuring social and emotional learning implementation in a research-practice partnership

Abstract: The measurement of social and emotional learning (SEL) implementation is a critical part of enhancing and understanding the effects of SEL programming. Research has shown that high-quality SEL implementation is associated with social, emotional, and academic outcomes. Schools achieve these outcomes in part through organizational practices that emphasize ongoing communication, collaboration, coordination, shared decision making, and strategic planning, processes that are ideally informed by evidence. The applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…"The teachers expressed the view that the role of the school heads should be mainly associated with the creation of a work environment that enhances the collaboration with the local community, fosters teamwork, mentoring and teacher participation in decision-making at school level as well as the facilitation of opportunities for teacher training and professional growth and development." [43] (p. [47][48]. In comparison, another study conducted in Greece has concluded that the more an organisation prioritises the creation of an environment that enables employees to learn at work, the higher the employees' satisfaction with their work [11].…”
Section: School Staff Job Satisfactionmentioning
confidence: 99%
“…"The teachers expressed the view that the role of the school heads should be mainly associated with the creation of a work environment that enhances the collaboration with the local community, fosters teamwork, mentoring and teacher participation in decision-making at school level as well as the facilitation of opportunities for teacher training and professional growth and development." [43] (p. [47][48]. In comparison, another study conducted in Greece has concluded that the more an organisation prioritises the creation of an environment that enables employees to learn at work, the higher the employees' satisfaction with their work [11].…”
Section: School Staff Job Satisfactionmentioning
confidence: 99%